2021
DOI: 10.1007/s00134-021-06352-y
|View full text |Cite
|
Sign up to set email alerts
|

How the COVID-19 pandemic will change the future of critical care

Abstract: Coronavirus disease 19 (COVID-19) has posed unprecedented healthcare system challenges, some of which will lead to transformative change. It is obvious to healthcare workers and policymakers alike that an effective critical care surge response must be nested within the overall care delivery model. The COVID-19 pandemic has highlighted key elements of emergency preparedness. These include having national or regional strategic reserves of personal protective equipment, intensive care unit (ICU) devices, consumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
161
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(166 citation statements)
references
References 72 publications
3
161
0
2
Order By: Relevance
“…Even after hospital visitor restrictions are relaxed, many family members will be unable to visit the ICU: it is increasingly common for family members to live in a different state than their loved one ( Douglas et al, 2016 ), and prior studies have shown that over half of family caregivers are also actively employed or lack ready transportation ( Carson et al, 2016 , Cox et al, 2019 ). While in-person communication can and should return to being the primary mode of family engagement once visitors return, virtual communication will continue to be of benefit for caregivers who cannot be present but wish to remain engaged ( Arabi et al, 2021 ). HCWs commented on the challenges of communicating with patients and families with Limited English Proficiency (LEP).…”
Section: Discussionmentioning
confidence: 99%
“…Even after hospital visitor restrictions are relaxed, many family members will be unable to visit the ICU: it is increasingly common for family members to live in a different state than their loved one ( Douglas et al, 2016 ), and prior studies have shown that over half of family caregivers are also actively employed or lack ready transportation ( Carson et al, 2016 , Cox et al, 2019 ). While in-person communication can and should return to being the primary mode of family engagement once visitors return, virtual communication will continue to be of benefit for caregivers who cannot be present but wish to remain engaged ( Arabi et al, 2021 ). HCWs commented on the challenges of communicating with patients and families with Limited English Proficiency (LEP).…”
Section: Discussionmentioning
confidence: 99%
“…A study from Arabi et al described different methods to expand the ICU staffing pool during the COVID-pandemic, e.g. optimizing ICU-nursing capacity by increasing the number of patients per nurse and the use of non-ICU staff to reinforce the ICU staff ( Arabi et al, 2021 ). Also in the Netherlands the ICU nurses were supported by non-ICU nurses for basic care, but the ICU nurses were still responsible for the wellbeing of a higher number of patients during their shift.…”
Section: Introductionmentioning
confidence: 99%
“…Alastair Watson PhD 1,2 Lucie Linhartova FRCA, FFICM 1 Paul Ellis MRCP 1 Rahul Mukherjee FRCP (London), FRCP (Edin. ), FCCP 1 1 Heartlands Hospital, University Hospitals Birmingham, UK…”
Section: Conflict Of Interestmentioning
confidence: 99%